Nitric Oxide (NO)-Releasing Macromolecules: Rational Design and Biomedical Applications - Cheng, Jian; He, Kewu; Shen, Zhiqiang; Zhang, Guoying; Yu, Yongqiang; Hu, Jinming (Frontiers in Chemistry, 2019)
Nitric oxide (NO) has been recognized as a ubiquitous gaseous transmitter and the therapeutic potential has nowadays received increasing interest. However, NO cannot be easily directly administered due to its high reactivity in air and high concentration-dependent physiological roles. As such, a plethora of NO donors have been developed that can reversibly store and release NO under specific conditions. To enhance the stability and modulate the NO release profiles, small molecule-based NO donors were covalently linked to polymeric scaffolds, rendering them with multifunctional integration, prolonged release durations, and optimized therapeutic outcomes. In this minireview, we highlight the recent achievements of NO-releasing macromolecules in terms of chemical design and biomedical applications. We hope that more efforts could be devoted to this emerging yet promising field.